2016
DOI: 10.1186/s12872-016-0347-7
|View full text |Cite
|
Sign up to set email alerts
|

Adverse clinical outcomes associated with a low dose and a high dose of aspirin following percutaneous coronary intervention: a systematic review and meta-analysis

Abstract: BackgroundGuidelines from the American Heart Association/American College of Cardiology recommend a higher dosage of aspirin daily following Percutaneous Coronary Intervention (PCI), whereas guidelines from the European Society of Cardiology recommend a lower dosage. This study aimed to compare the adverse clinical outcomes associated with a low dose and a high dose of aspirin following PCI.MethodsElectronic databases were searched for studies comparing a low dose with a high dose aspirin following PCI. Advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Although we expected a higher incidence of major bleeding associated with high-dose aspirin compared to low-dose aspirin, our data did not show any difference in major bleeding between the 2 doses. A prior study found that high-dose aspirin had significantly more Thrombolysis in Myocardial Infarction (TIMI) defined minor bleeding after percutaneous coronary intervention compared to low-dose aspirin [66]. Laine et al [79] did not find an increase in gastric ulceration when low-dose aspirin (81 mg/d) was used in osteoarthritic patients for 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we expected a higher incidence of major bleeding associated with high-dose aspirin compared to low-dose aspirin, our data did not show any difference in major bleeding between the 2 doses. A prior study found that high-dose aspirin had significantly more Thrombolysis in Myocardial Infarction (TIMI) defined minor bleeding after percutaneous coronary intervention compared to low-dose aspirin [66]. Laine et al [79] did not find an increase in gastric ulceration when low-dose aspirin (81 mg/d) was used in osteoarthritic patients for 12 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…A systematic review and meta-analysis by Bundhun et al investigated the clinical outcomes after treatment of high-dose vs low-dose aspirin following percutaneous coronary intervention. The study found a higher association of major adverse cardiac events such as death, myocardial infarction (MI), and revascularization when high-dose aspirin was given compared to low-dose aspirin [66]. Additionally, Taylor et al [67] found a decreased risk of stroke, MI, and death within 30 days and 3 months after carotid endarterectomy when patients were treated with low doses of aspirin (81 or 325 mg/d) compared to higher doses (650 or 1300 mg/d).…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Previous guidelines of CAD treatment emphasised on emergency treatment PCI treatment should be supplemented with antiplatelet agents, which may prevent formation of coronary thrombus. [ 26 , 27 ] CAG is also used to detect coronary artery stenosis, and it shows the coronary dominance at the same time. [ 28 ] Scoring system was usually used to evaluated the severity of coronary artery stenosis in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, these adverse outcomes might not always be dependent on the types of stents that were implanted. Several other studies have shown that the types of patients who were involved, [ 28 , 29 ] age of the patients, the comorbidities, and complications which were present before or following PCI, [ 30 32 ] the types of anti-platelets that were used and the duration period of DAPT, [ 33 , 34 ] the dosage of aspirin that was used, [ 35 ] could all contribute to and have a great impact on the adverse clinical outcomes following PCI.…”
Section: Discussionmentioning
confidence: 99%